2012
DOI: 10.1111/j.1461-9563.2012.00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Eucalyptus susceptibility to the gall‐forming wasp Leptocybe invasa

Abstract: 1 Extensive variation to damage by the invasive gall-forming wasp Leptocybe invasa Fisher & LaSalle (Hymenoptera: Eulophidae) is known to exist amongst Eucalyptus genotypes. 2 In the present study, 30 of the 50 tested genotypes were susceptible to gall formation and development of the wasp. Gall development on the petiole and leaves of plants was compared to calculate the percentage of infestation per plant and per genotype. 3 A positive correlation between galls on petioles and leaves indicated an absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 14 publications
0
45
0
2
Order By: Relevance
“…One of the first reported cases where this approach was applied is where eucalypt growers in South Africa replaced E. viminalis with other species due to its high susceptibility to Gonipterus sp., as well as the leaf pathogen Teratosphaeria (= Mycosphaerella) nubilosa (Tooke 1955;Hunter et al 2008). More recently, there have been numerous trials to screen for resistance of current and potential commercial genotypes to the relatively new introductions of L. invasa (Phạm Quang Thua et al 2009;Javaregowda and Prabhu 2010;Nyeko et al 2010;Dittrich-Schröder et al 2012;Zheng et al 2014) and O. maskelli (Protasov et al 2007). In the case of L. invasa, the high level of susceptibility to E. grandis x camaldulensis clones in South Africa has led to a preference for planting E. grandis x urophylla hybrids in infested areas.…”
Section: Spread For Example Guidelines Proposed Under the Internatimentioning
confidence: 99%
“…One of the first reported cases where this approach was applied is where eucalypt growers in South Africa replaced E. viminalis with other species due to its high susceptibility to Gonipterus sp., as well as the leaf pathogen Teratosphaeria (= Mycosphaerella) nubilosa (Tooke 1955;Hunter et al 2008). More recently, there have been numerous trials to screen for resistance of current and potential commercial genotypes to the relatively new introductions of L. invasa (Phạm Quang Thua et al 2009;Javaregowda and Prabhu 2010;Nyeko et al 2010;Dittrich-Schröder et al 2012;Zheng et al 2014) and O. maskelli (Protasov et al 2007). In the case of L. invasa, the high level of susceptibility to E. grandis x camaldulensis clones in South Africa has led to a preference for planting E. grandis x urophylla hybrids in infested areas.…”
Section: Spread For Example Guidelines Proposed Under the Internatimentioning
confidence: 99%
“…This variation in infestation may be environmental, but a large component is genetic controlled (Nadel & Slippers, 2011). Mutitu et al (2010) and Dittrich-Schröder, Wingfield, Hurley, and Slippers (2012) Nyeko et al (2010) reported that out of 24 Eucalyptus germplasms evaluated for L. invasa infestations in Busia, Kenya, E. henryi was resistant, E. camaldulensis and E. urophylla were tolerant while E. tereticornis, E. grandis, and E. saligna were moderately susceptible to the pest. Leptocybe invasa infestation differences in the same species in different sites may be attributed to differences in climatic variables, provenances, soil factors, silvicultural practices, and crop type (coppice against first crop ;Nyeko et al, 2010).…”
Section: Infestation Density Of L Invasa On Different Eucalyptus Spementioning
confidence: 99%
“…Similarly, Mendel et al (2004) reported the same, that eucalypt seedlings in the nurseries, saplings in plantations, and coppiced shoots in plantations are more susceptible to L. invasa attack. In South Africa, L. invasa attacks trees of all ages, from nursery stock to mature trees, but the damage is most severe on younger plants (Dittrich-Schröder et al, 2012). Kumari et al (2010) reported the same in India, that L. invasa was more severe in young trees than on 6-yr-old trees.…”
Section: Variation Of L Invasa Infestation Densities Between Tree Agmentioning
confidence: 99%
“…A reprodução do tipo partenogênese telítoca e o desenvolvimento multivoltino (4 a 6 gerações ano -1 ), aliado à ausência de inimigos naturais, propiciaram uma rápida expansão pelos continentes (MENDEL et al, 2004;KIM et al, 2008). Infestações mais severas foram verifi cadas em genótipos cujo pico de crescimento corresponde ao período de emergência e oviposição desta microvespa e em regiões de baixa altitude, quentes e secas (MENDEL et al, 2004;NYEKO et al, 2009;DITTRICH-SCHRÖDER et al, 2012).…”
unclassified
“…O manejo de L. invasa em áreas comerciais de eucalipto está direcionado principalmente para o uso de materiais resistentes e estratégias ligadas ao controle biológico (DITTRICH-SCHRÖDER et al, 2012), uma vez que o controle químico é considerado inefi ciente, além de afetar os inimigos naturais (GOWDA et al, 2010 (KIM et al, 2008;PROTASOV et al, 2008;KULKARNI et al, 2010;KELLY et al, 2012).…”
unclassified